Allelic variants of human genes affecting HIV intracellular life cycle and regulating immune response to HIV infection - R. M. Khaitov; L. P. Alexeev; G. O. Gudima; I. A. Kofiadi (Бюллетень сибирской медицины)
Host genetic factors influencing the intracellular part of HIV live cycle and regulating of HIV-specific immune response are reviewed. Its include genes coding proteins which support viral replication and assembly of new virions, genes coding antiviral defense proteins, HLA genes and some others. Variants of these genes and its compositions affect individual succeptibility/resistance to HIV infection, influence the pathogenesis of the disease and also associate with efficacy of antiretroviral therapy.